Pendidikan Pancasila dan Kewarganegaraan sebagai Optimalisasi dalam Meningkatkan Sikap Toleransi Siswa - Ture Ayu Situmeang; Laras Sati Sintania; Murniwati Lase; Sri Yunita (Journal on Education, 2023)
PPKn as a curricular education program essentially aims to form good citizens. The existence of PPKn in the student learning process itself is closely related to the formation of civic character which is instilled in individual students through a value-based approach to students in order to achieve the attributes of civil society characterized by belief in God. almighty, just and civilized humanity. Therefore this study aims to describe how the role of Pancasila and civics education in optimizing tolerance among students at Teladan Private High School in Medan. the method used is descriptive qualitative method with the use of primary data sources.